Using Songs to improve vocabulary learning in the english language with students of 4th and 5th year of basic education at Dr. Luis Emilio Rodriguez school. Academic period 2013-2014 - Labanda Cabrera, Ivan Patricio (2015)
This descriptive study investigated the use of songs in the improvement of English-vocabulary learning with fourth and fifth year students at Dr. Luis Emilio Rodriguez School. An intervention plan with eleven sessions was implemented to improve this sub skill. A researcher’s-made test was designed and used to measure the eight students’ progress and perception of songs. Additionally instruments like observation sheets were also used along the process to monitor the students’ growth. The results showed that the use of songs facilitated meaningfully the improvement of vocabulary learning which was reflected in the increase of the posttest scores and students’ progress during the intervention. The answers from the checklists confirmed the enthusiasm and the positive attitude toward working with vocabulary. In conclusion this study helped students to improve their vocabulary learning, the researcher to sharpen his teaching skill and the community to have better professionals.